Application of X-ray Microtomography in Dental Science - Gabriel José Costa Teles; Alessandra Machado; Ricardo Lopes (Brazilian Journal of Radiation Sciences)
This study delves into the application of X-ray microtomography (microCT) in dental sciences, displaying its ability to provide detailed and non-destructive three-dimensional images of dental structures. Two primary studies were conducted: the first study examined the formation of dentinal cracks after root canal instrumentation in lower molars using different mechanized systems and evaluated the presence of debris after instrumentation. The second study assessed the removability of bioceramic cement combined with gutta-percha in lower premolars and quantified the remaining material after re-instrumentation of the canals. The results demonstrated that microCT is an essential tool for identifying cracks with micrometric precision and quickly quantifying debris and remaining obturation materials, underscoring its effectiveness in dental diagnosis and research. The research highlights the potential of microCT to enhance clinical outcomes in dentistry, significantly contributing to the development of new treatment techniques and materials. It suggests that this technology will become increasingly accessible and widely adopted.